New species of Lebiasina (Ostariophysi: Characiformes: Lebiasinidae) from the upper Mazaruni River drainage, Guyana - Netto-Ferreira, André L.; Lopez-Fernandez, Hernán; Taphorn, Donald C.; Liverpool, Elford A. (Zootaxa, 2013)
Lebiasina ardilai is described from the upper Mazaruni in Guyana. The new species differs from all its congeners by its color pattern consisting of: a narrow, nearly straight primary stripe, extending from posterior to humeral blotch to near the vertical through anal-fin origin, being absent or inconspicuous in females and conspicuously marked in males; the pres-ence of four series of dark blotches at the distal border of the scales of longitudinal series 2–5; the faint secondary stripe running onto scales of second and third longitudinal row of scales; intermediate stripe absent; and the posteriorly displaced caudal blotch, not reaching the posterior tip of caudal peduncle.